2015
DOI: 10.1016/j.ejphar.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pulmonary sigma receptors by radioligand binding

Abstract: This study establishes the expression of appreciable populations of sites on mouse lung membranes that exhibit radioligand binding properties and pharmacology consistent with assignment as sigma1 and sigma2 receptors. Specific binding of the sigma1 receptor radioligand [3H](+)-pentazocine reached steady state within 6 h at 37 °C. Saturation studies revealed high affinity binding to a single class of sites (Kd 1.36 ± 0.04 nM; Bmax 967 ± 11 fmol / mg protein). Inhibition studies showed appropriate sigma1 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…In agreement with earlier results (Lever et al, ), [ 125 I] E ‐IA‐DM‐PE‐PIPZE displayed good levels of control specific binding (Fig. ) to σ 1 receptors in brain (83%), heart (53%), lung (66%), and spleen (71%).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with earlier results (Lever et al, ), [ 125 I] E ‐IA‐DM‐PE‐PIPZE displayed good levels of control specific binding (Fig. ) to σ 1 receptors in brain (83%), heart (53%), lung (66%), and spleen (71%).…”
Section: Resultssupporting
confidence: 92%
“…Biodistribution studies of [ 125 I] E ‐IA‐DM‐PE‐PIPZE binding to σ 1 receptors (Lever et al, ) and [ 125 I]RTI‐121 binding to the DAT (Desai et al, ; Lever et al, ) were conducted as previously reported. In general, awake animals received tail vein injections of radioligands (2.5 μCi) formulated in saline (0.1 mL) containing 2% ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 125 I]- E -IA-BF-PE-PIPZE uptake was reduced significantly by E -IA-BF-PE-PIPZE (53% – 94%), haloperidol (47% – 90%) and BD1063 (53% – 90%) in brain and peripheral organs, with the exception of the liver. Expression of σ 1 receptors by all of these organs has been confirmed in prior in vitro or in vivo studies [42,55,140,145]. The liver showed increased uptake upon inhibition of σ 1 receptor binding in the other organs.…”
Section: In Vivo Evaluationsupporting
confidence: 56%
“…However, a 5.7-fold higher affinity ( K d 0.042 nM) was calculated for [ 125 I]- E -IA-BF-PE-PIPZE using rate constants compared to saturation binding ( K d 0.24 nM). Such discrepancies are frequently observed [93,137140]. Agreement can be improved in some cases by correcting for radioligand depletion, either mathematically or by using low receptor concentrations [137,138].…”
Section: Direct Receptor Bindingmentioning
confidence: 99%